REDUNCINE FOSSILS FROM THE UPPER SIWALIKS OF TATROT - M. A. Khan; A. M. Khan; M. Iqbal; M. Akhtar; S. Mahboob (Journal of Animal and Plant Sciences, 2008)
Fossil remains of the reduncines are preserved in the Siwalik Tatrot Formation of northern Pakistan. The Tatrot fauna is dominated by the bovids, represent most abundant taxa found from the Siwaliks. These specimens were discovered by the first author in the well dated late Pliocene deposits of the Potwar Plateau, northern Pakistan. The Pliocene deposits of the Tatrot Formation yielded fossil remains of reduncines, which are now grazing antelopes found in habitats associated with the vicinity of water. This discovery adds weight to the suggestion that the Pliocene reduncines inhabited the riverine galleys rather than the dry regions and moreover the sedimentary deposits of the Tatrot were the wetland area during the Pliocene epoch that documents the ancient biome.
Keywords: Reduncine; Bovids; Pliocene; Siwaliks; Tatrot.